The making of LGBTQ+ leaders in an international bank : obstacles and strategies to career progression - Goyal, Akansha; Bruscemi, Jacinthe; Talbot, Evan; Roulet, Thomas (Thomas J.) (London : University of Cambridge, Judge Business School, 2024)
Pinkbank, a large international bank based in the UK, has been prominent in supporting the LGBTQ+ community. The company has developed extensive policies regarding diversity and inclusion of this community. The bulk of these policies have been focused on developing HR equality policies, equal benefits for employees such as equal pay, anti-discrimination policies, and setting up employee resource groups and networks. Pinkbank has also taken actions outside the company walls to promote the rights of LGBTQ+ members including advertising same-sex couples, closing bank accounts of customers displaying anti-LGBTQ+ behaviours, and supporting pride events. The company has been internationally recognised, being regularly ranked among the top pro-LGBTQ+ organisations, and being rewarded with LGBTQ+ awards. Pinkbank has made significant progress to date, but there are still gaps with diversity lacking at the top and numerous hurdles that the LGBTQ+ community faces to climb up the corporate ladder. In particular, there is a lack of role models and mentors in senior positions who could inspire LGBTQ+ members to climb to the top. Aside from the structural impediments to advancement at Pinkbank, there is an apparent lack of data on the LGBTQ+ talent pool. Other obstacles to progression include mental barriers such as self-censoring and a lack of trust. Based on interviews with numerous ambitious members of the LGBTQ+ community at Pinkbank, they employed unique approaches to rise above the many obstacles. Through three protagonists' experiences, we see how the LGBTQ+ workforce is not static and has crafted innovative strategies to address these breakdowns. Networking is a powerful tool to connect not only with individuals from the same community sharing the same burdens, but also with allies outside of the community, helping LGBTQ+ employees leverage their knowledge and progress within the company. Capitalising on their unique experience and position is another powerful tool. LG
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bank management -- Case studies; Diversity in the workplace -- Case studies; Sexual minority business enterprises -- Case studies